2017
DOI: 10.1128/aem.00729-17
|View full text |Cite
|
Sign up to set email alerts
|

Response of Microbial Community Function to Fluctuating Geochemical Conditions within a Legacy Radioactive Waste Trench Environment

Abstract: During the 1960s, small quantities of radioactive materials were codisposed with chemical waste at the Little Forest Legacy Site (Sydney, Australia) in 3-meter-deep, unlined trenches. Chemical and microbial analyses, including functional and taxonomic information derived from shotgun metagenomics, were collected across a 6-week period immediately after a prolonged rainfall event to assess the impact of changing water levels upon the microbial ecology and contaminant mobility. Collectively, results demonstrated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…Notably, the Venn diagram analysis showed that the phylum Omnitrophica was specifically enriched in both CB (0-40 cm) and CS (20-40 cm) (data not shown). Omnitrophica, belonging to the Planctomycetes-Verrucomicrobia-Chlamydiae (PVC) superphylum, was probably involved in the removal of recalcitrant substances in the contaminated sites 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the Venn diagram analysis showed that the phylum Omnitrophica was specifically enriched in both CB (0-40 cm) and CS (20-40 cm) (data not shown). Omnitrophica, belonging to the Planctomycetes-Verrucomicrobia-Chlamydiae (PVC) superphylum, was probably involved in the removal of recalcitrant substances in the contaminated sites 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to better understand the archaeal contributions in LFLS groundwaters and their influence upon site biogeochemistry, raw sequencing reads from ENA project PRJEB14718 ( Vázquez-Campos et al, 2017 ) were reanalysed using genome-based metagenomic methodologies. Briefly, samples were collected in triplicate over a period of 47 days at four time-points, i.e., 0 (SAMEA4074280–2), 4 (SAMEA4074283–5), 21 (SAMEA4074286–8), and 47 (SAMEA4074289–91) days, after an intense rainfall event that filled the trench.…”
Section: Methodsmentioning
confidence: 99%
“…An unintended consequence of this, is that surface water infiltrates into the more porous trench waste form at a greater rate when compared to the surrounding geology, and during intense and prolonged rainfall events the contaminated water levels in trenches fill up, akin to a ‘bathtub’ ( Payne et al, 2013 , 2020 ). Aside from providing a mechanism enabling the export of contaminants, occurring when trench waters (infrequently) overflow out of the ‘bathtub’ to the surrounding environment ( Payne et al, 2013 ), the periodic influx of oxic waters into these natural reducing zones results in transitory microbial population shifts associated with pronounced elemental cycling ( Vázquez-Campos et al, 2017 ; Kinsela et al, 2021 ). Our previous research showed that the archaeal community in the LFLS waste trenches, while constituting a minor portion of the whole microbial community, included a number of potentially interesting members, either in terms of phylogeny and/or functionality ( Vázquez-Campos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that mobilization of Pu from the trenches is related to complex interactions between the influx of oxidizing groundwater during rainfall and the subsequent extended period of reducing conditions. The microbial activity influences the distributions of actinides and other redox-sensitive elements, such as iron and manganese (Vázquez-Campos et al, 2017 ). The study shows seasonal changes in redox conditions, which can significantly change the migration of redox-sensitive actinides, especially Pu.…”
Section: Plutoniummentioning
confidence: 99%